Mobile Based Rumbai Flood And Broken Drainage Reporting System Using Exteme Programming - Aziz Kandias; Shumaya Resty Ramadhani; Retno Tri Wahyuni (International ABEC, 2022)
Floods and broken drainage are often experienced by the community, but only a few people report these cases by reporting directly to the local government which takes a long time because they must report the cases with official letter. Besides that, most people do not know where and how to report cases of flood and broken drainage. On the other hand, Pekanbaru Public Works Agency (PUPR) handles, and updates reports through internal WhatsApp group so that report updates are not stored in a structured way and public community cannot see the updates directly. Because of the problem above a system is needed to handle the problem, the system that is going to be created implemented extreme programming methodology and built with flutter for fastest development that covering both IOS and Android devices and expected to facilitate easy access and speeds up the process for creating reports from the public community and the PUPR officer to flood or broken drainage and could provide and record up-to-date data and status of the reports. Based on the results of testing, that is unit, integration and black box testing found that the functionality of the system was going well. Then, for usability testing with the SUS method, the results were 78. Based on the usability testing, it can be concluded that the system that has been created is categorize as good acceptable and it can help public community to simply create flood and broken drainage report also provide the up-to-date report of submitted report.